Algorithm of magnetic flux density on a plane generated by a finite length current source / Rashdi Shah Ahmad, Tahir Ahmad and Chew Soon Leong - Ahmad, Rashdi Shah; Ahmad, Tahir; Chew, Soon Leong (Fakulti Teknologi Maklumat dan Sains Kuantitatif, 2001)
The magnetic isofield pattern is very important in the field of magnetoencephalography. The pattern can assist in determining the location of the current sources. In this paper a program written in MATLAB environment, togenerate the isofield pattern on a plane above a finite length current source, is described.